Dynamics of the African Plate 75 Ma: From Plate Kinematic Reconstructions to Intraplate Paleo‐Stresses. Issue 7 (23rd July 2021) - Wouters, Marius C.; Pérez‐Díaz, Lucía; Tuck‐Martin, Amy; Eagles, Graeme; Adam, Jürgen; Govers, Rob
Abstract: Plate reconstruction studies show that the Neotethys Ocean was closing due to the convergence of Africa and Eurasia toward the end of the Cretaceous. The period around 75 Ma reflects the onset of continental collision between the two plates as convergence continued to be taken up mostly by subduction of the Neotethys slab beneath Eurasia. The Owen transform plate boundary in the northeast accommodated the fast northward motion of the Indian plate relative to the African plate. The rest of the plate was surrounded by mid‐ocean ridges. Africa was experiencing continent‐wide rifting related to northeast‐southwest extension. We aim to quantify the forces and paleostresses that may have driven this continental extension. We use the latest plate kinematic reconstructions in a grid search to estimate horizontal gravitational stresses (HGSs), plate boundary forces, and the plate's interaction with the asthenosphere. The contribution of dynamic topography to HGSs is based on recent mantle convection studies. We model intraplate stresses and compare them with the strain observations. The fit to observations favors models where dynamic topography amplitudes are smaller than 300 m. The results also indicate that the net pull transmitted from slab to the surface African plate was low. To put this into context, we notice that available tectonic reconstructions show fragmented subduction zones and various colliding micro‐continents along the northern margin of the African plate around this time. We therefore interpret a low net pull as resulting from either a small average slab length or from the micro‐continents' resistance to subduction. Key Points: Deformation of the African plate 75 Ma was mainly driven by horizontal gravitational stress, transform shear and weak slab pull The weak pull from the Neotethys slab indicates that the slab was short or the pull was reduced by mantle resistance or by slab buoyancy The complex closure history of the Neotethys Ocean is a likely candidate for the limited pull magnitude